The Development of Blood Bank Application - Alamgir, Wahab; Rozlini Mohamed (Applied Information Technology And Computer Science, 2022)
Blood bank Application is a public interest project aiming to deliver the facility of swift inventory transfer across the clustered network. This facilitates the health sector in managing, safe utilizing, and transfusing life critical product Blood. Blood bank Application is Database Driven Web Application with augmentation of advance facilities to health sector specially blood banks which are not currently offered by any agency till date. Swift Inventory Transfer Facility is the core area of the project. Project will implement the Blood Inventory in highly access controlled environment along with all the necessary data of blood, integrated during the life cycle of the item (Blood). This project is an enhanced variant project of Blood Bank Application with enrich feature of managing the blood bags along with the donor details. Blood Bank Application is public interest project and of very significant cause, that is to achieve transparency, prompt-availability, and controlled transfusion of blood across the country with utilization of minimum human and capital resources